2005
DOI: 10.1081/ja-200066960
|View full text |Cite
|
Sign up to set email alerts
|

Ecstasy Use Among Hispanic and Black Substance Users in New York City

Abstract: Surveillance data suggests that use of ecstasy in the U.S. is predominantly among white adolescent and young adults. To investigate ecstasy use among substance users in New York City we added questions to ongoing efforts to recruit heroin and cocaine users. Of 715 participants recruited, 58.3% were injection drug users (IDUs). The median age was 32 (range 17-64), 76.4% were male, 49.0% were currently homeless, 62.4% were Hispanic, 27.3% were black, and 34.5% were born outside the United States. Overall, 23.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…These locations were then chosen as sites of recruitment. Recruitment was conducted through targeted sampling with street outreach techniques (Diaz et al, 2001a,b; Ompad et al, 2005). Study recruiters were residents of the same neighborhoods from which participants were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…These locations were then chosen as sites of recruitment. Recruitment was conducted through targeted sampling with street outreach techniques (Diaz et al, 2001a,b; Ompad et al, 2005). Study recruiters were residents of the same neighborhoods from which participants were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Boeri and colleagues noted the use of Ecstasy in settings other than raves, including clubs and bars as well as in private homes, and among non-white users (Boeri, Sterk, & Elifson, 2004). Other studies have shown increased use of Ecstasy use among other ethnic groups (Eiserman, Diamond, & Schensul, 2005; Ompad, Galea, Fuller, Edwards, & Vlahov, 2005; Schensul et al, 2005) and in various socio-economic settings (Schensul et al, 2005; Yacoubian, 2003; Yacoubian et al, 2002). The U.S. Office of National Drug Control and Policy found that Ecstasy sales had increased in some African-American communities as well as among Asian gangs in certain parts of the country (ONDCP, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…The majority of independent variables were chosen based on previous epidemiologic studies on ecstasy using logistic regression analysis ( Boyd et al, 2003;Corapcioglu & Ogel, 2004;Degenhardt et al, 2004;Keyes et al, 2008;Ompad et al, 2005;Pedersen & Skrondal, 1999;Wu et al, 2006;Wu et al, 2009a) These were: age (categorized into three groups: 15-24, 25-34 and 35 years or older), gender, country of birth (born in Sweden or not), urbanicity (categorized into: living in a larger city (i. e., Stockholm, Gothenburg or Malmo), living in a suburb of a larger city, and other), income (above median or not), educational level (above high school level or not), housing status (living with one's partner or not), hazardous alcohol use, habitual smoking (smoking daily or having done so previously during at least six months), frequency of nights out (i. e., visiting a bar, night club or pub during the past 12 months, categorized into: twice a week or more, 2-4 times a month, and once a month or less) and lifetime illicit use of other drugs: cannabis, stimulants (amphetamine and cocaine), heroin (this category also included methadone and buprenorphine) and prescription drugs.…”
Section: Methodsmentioning
confidence: 99%
“…With few exceptions (Wu et al, 2009a;Wu, Parrott, Ringwalt, Yang, & Blazer, 2009b), most studies reporting correlates of ecstasy use have been conducted on perceived high-risk groups, such as youths (Degenhardt, Barker, & Topp, 2004;Keyes, Martins, & Hasin, 2008;Pedersen & Skrondal, 1999;Wu, Schlenger, & Galvin, 2006), students (Boyd, McCabe, & d'Arcy, 2003;Corapcioglu & Ogel, 2004) and illicit drug users (Ompad, Galea, Fuller, Edwards, & Vlahov, 2005). The aim of the present study was, therefore, to add to previous epidemiological studies on ecstasy use by reporting correlates of ecstasy use in the Swedish general population.…”
Section: Introductionmentioning
confidence: 99%